Kontribusi Power Otot Tungkai dan Koordinasi Mata Kaki terhadap Ketepatan Shooting Atlet Bhinneka Futsal Majenang - Husna Syarifful Amin; Cucu Hidayat; Herdi Hartadji (e-SPORT: Jurnal Pendidikan Jasmani, Kesehatan dan Rekreasi, 2023)
One of the basic techniques in futsal that play an important role is shooting strokes. This study aims to determine how much the contribution of leg muscle power and ankle coordination to shooting accuracy in the futsal game of Bhinneka Futsal Majenang athletes. This study uses a quantitative descriptive method. The population in this study were Bhinneka Futsal athletes, totaling 43 people. 18 athletes were selected as samples by purposive sampling technique. The instruments used were tests and measurements of standing long jump, soccer wall volleyball test, and shooting accuracy. The test results show a contribution. The hypothesis test shows that the f count is 10.2 > f table 3.65 = 4.46. Therefore, this shows that Ho is rejected and Ha is accepted, which means that there is a significant contribution between leg muscle power and ankle coordination on shooting accuracy. Keywords: Futsal, Ankle Coordination, Leg Muscle Power, Shooting